Pengaruh Good Corporate Governance Terhadap Harga Saham Perusahaan Manufaktur Subsektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022 - Octa Viorica Aulia Putri; Susi Sarumpaet (Pusat Riset dan Inovasi Nasional, 2024)
The development of the globalization era affects the capital market, additional capital is very necessary to improve company performance. Companies can offer ownership to the public through the capital market to increase company capital. This research was conducted to test whether there is an influence of good corporate governance on share prices. The variables used in the research include managerial ownership, institutional ownership and the board of directors. The research was conducted using a population of financial report data from companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period, including 45 data samples. According to research findings, managerial ownership has a significant positive effect on share prices, institutional ownership has a significant positive effect on share prices and the board of directors has a significant negative effect on share prices. The limitations of this research lie in the sample and length of the research. The research only used a sample of manufacturing companies in the food and beverage subsector with a research period of 2018-2022.